2016
DOI: 10.1038/srep36888
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic adaptation of small intestinal mucosa in response to dietary protein limitation

Abstract: Dietary protein limitation (PL) is not only beneficial to human health but also applied to minimize nitrogen excretion in livestock production. However, the impact of PL on intestinal physiology is largely unknown. In this study, we identified 5275 quantitative proteins using a porcine model in which pigs suffered PL. A total of 202 proteins |log2 fold-change| > 1 were taken as differentially expressed proteins and subjected to functional and pathway enrichment analysis to reveal proteomic alterations of the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Pigs were given free access to feed and water. During the period of the study, the feed intake (kg d –1 ) remained unchanged, and final BW was decreased upon moderate PR as described previously …”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Pigs were given free access to feed and water. During the period of the study, the feed intake (kg d –1 ) remained unchanged, and final BW was decreased upon moderate PR as described previously …”
Section: Methodsmentioning
confidence: 86%
“…Most previous studies focused on extremely protein restrictive diets, in which protein levels were reduced by about 60–100%, or on specific essential amino acid (EAA), such as methionine and branched‐chain AA, which were restricted by 50% or more, far below the estimated average requirement for human and rodents, likely unsustainable and unhealthy due to the severe deficiency of EAA . We demonstrated that moderate PR diets, whose protein levels were reduced by about 20%, shrank circulating AA pool size and profoundly altered the pathways concerning immune function in the small intestine even with the supplementation of crystal EAA in diets . However, the impact of moderate PR without malnutrition on insulin resistance remains unclear.…”
Section: Introductionmentioning
confidence: 85%
“…To explore the alteration of lipogenesis and lipid accumulation in skeletal muscle, the relative protein expression levels of phosphor-adenosine monophosphate-activated protein kinase α (p-AMPKα), AMPKα, phosphor-acetyl coenzyme A (p-ACC), ACC, peroxisome proliferator activated receptor-γ (PPARγ) and CAAT/enhancer binding protein α (C/EBPα) in the LDM were determined by western blot analysis using the protein samples from all individual animals ( n = 6) as described previously [24]. Briefly, equal amounts of samples (50 μg of protein), together with a pre-stained protein ladder (Thermo Fisher, Rockford, IL, USA), were subjected to sodium dodecyl sulfate polyacrylamide gel electrophoresis electrophoresis with glyceraldehyde 3-phosphate dehydrogenase (GAPDH) being run as a loading control.…”
Section: Methodsmentioning
confidence: 99%
“…Diet has a broad influence on the small intestine. For example, protein limitation in diet can upregulate the proteins involved in protein/carbohydrate digestion, intestinal mucosal tight junction and cell adhesion, and the immune response to foreign antigens in the jejunal mucosa of pigs, but downregulate amino acid transport, innate and auto immunity, as well as cell proliferation and apoptosis [38] . In the present study, GO and KEGG pathway analyses indicated that, under the normal dose, intake of chicken protein induced upregulation of respiratory chain, oxidative phosphorylation and oxidoreductase activity, cell junction organization, and regulation of proton transport.…”
Section: Discussionmentioning
confidence: 99%